2010
DOI: 10.1007/s11355-010-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

A forest-structure-based analysis of rain flow into soil in a dense deciduous Betula ermanii forest with understory dwarf bamboo

Abstract: The relationship between rain flow into the soil and forest structure was investigated in a dense deciduous Betula ermanii forest in northern Japan. The forest floor was covered with dwarf bamboo Sasa kurilensis. Observation was conducted from mid-July to late October in 1998. Leaf fall of Betula started in early September and ended in late October. Stemflow was proportional to rainfall and tree size [diameter at breast height (DBH)], and for the same rainfall, stemflow increased with leaf fall. On the contrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In a birch forest of northern Japan, K . Takahashi et al . [2011] found that stand level stemflow increased with tree diameter but decreased with stand leaf mass.…”
Section: Stemflow Yield and Chemistry In Relation To Canopy Structurementioning
confidence: 99%
“…In a birch forest of northern Japan, K . Takahashi et al . [2011] found that stand level stemflow increased with tree diameter but decreased with stand leaf mass.…”
Section: Stemflow Yield and Chemistry In Relation To Canopy Structurementioning
confidence: 99%
“…Some studies have included canopy position, (Reynolds and Henderson, 1967;Aboal et al, 1999;Terra et al, 2018) or neighbouring tree proximity (McKee and Carlyle-Moses, 2017) in tree stemflow models, whereas Krämer and Hölscher (2009) tested species composition effects on area average stemflow. Other studies have discussed a shading effect in the lower canopy (André et al, 2008;Takahashi et al, 2011) as a possible explanation for their stemflow results. However, a systematic study explicitly focusing on neighbourhood effects on stemflow in a quantitative approach is currently missing.…”
Section: Introductionmentioning
confidence: 97%
“…tree-to-tree) variability, and thus inherently implied temporally stabile drivers. Most prominently, tree diameter (or circumference, basal area, crown projection area) has been identified as a factor shaping tree-specific stemflow within an event (Reynolds and Henderson, 1967;Aboal et al, 1999;André et al, 2008;Krämer and Hölscher, 2009;Takahashi et al, 2011). However, stemflow yield still shows a great deal of between-tree variation after accounting for tree size (Reynolds and Henderson, 1967;Takahashi et al, 2011;McKee and Carlyle-Moses, 2017), as trees' traits related to morphology and crown architecture additionally affect individual tree stemflow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, research on Betula during the past 5-6 years has mostly been in the area of ecology and silviculture (261/339 publications or 77%). Examples of ecological papers include birch community and ecosystem analysis (Kleczewski et al 2010;Deslippe et al 2011;Takahashi et al 2011), regeneration, vegetation succession and human influence (Shrestha et al 2007;Erlendsson & Edwards 2009;Schofield & Edwards 2011), impact of climate change on plant performance and productivity (Levanic & Eggertsson 2008;Pudas et al 2008;Sano et al 2010), modelling of plant structure, growth and phenology (Linkosalo et al 2010;Caffarra et al 2011;Lintunen et al 2011), environmental pollution and chemical ecology (Kontunen-Soppela et al 2010;Franiel & Babczynska 2011;Morales et al 2011). Although the category ecology-physiology appears to be the most published subject, a good proportion of the studies have direct application in silviculture and forestry.…”
Section: Birch (Betula L)mentioning
confidence: 99%